2018
DOI: 10.1111/hae.13493
|View full text |Cite
|
Sign up to set email alerts
|

Individual thrombin generation and spontaneous bleeding rate during personalized prophylaxis with Nuwiq®(human‐cl rhFVIII) in previously treated patients with severe haemophilia A

Abstract: In adults with severe haemophilia A and reduced thrombin generation, increased frequency of spontaneous bleeding was observed irrespective of trough FVIII levels. Thus, personalized prophylaxis should take into account variables other than FVIII:C. Large prospective trials are needed to verify ETP as a marker for spontaneous bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 34 publications
4
36
0
Order By: Relevance
“…This approach has recently been tested in a study that showed an increased frequency of spontaneous bleeding in HA patients with reduced TG regardless of FVIII trough levels when patients were on personalized prophylaxis with human-cl rhFVIII (Nuwiq). 9 A follow-up study postulated a PK/PD non-linear relationship between FVIII and ETP, thereby creating a dosing tool for this FVIII product to even further personalize FVIII prophylaxis. 40 Our goal is to use our PD data to develop a uniform model to individualize FVIII replacement therapy based on PK/PD data for a range of FVIII products.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…This approach has recently been tested in a study that showed an increased frequency of spontaneous bleeding in HA patients with reduced TG regardless of FVIII trough levels when patients were on personalized prophylaxis with human-cl rhFVIII (Nuwiq). 9 A follow-up study postulated a PK/PD non-linear relationship between FVIII and ETP, thereby creating a dosing tool for this FVIII product to even further personalize FVIII prophylaxis. 40 Our goal is to use our PD data to develop a uniform model to individualize FVIII replacement therapy based on PK/PD data for a range of FVIII products.…”
Section: F I G U R Ementioning
confidence: 99%
“…However, some patients still experience bleeding episodes despite adequate FVIII trough levels 6 . In general, severity of bleeding phenotype is roughly correlated with measured FVIII activity level but can vary between individual patients with an equal FVIII activity level 7‐9 . The underlying difference in bleeding phenotype and response to replacement therapy is yet to be determined, with individual variations in the hemostatic balance as a potential leading cause.…”
Section: Introductionmentioning
confidence: 99%
“…For PK data, plasma FVIII:C was measured at a central laboratory (LabCorp) using a one‐stage assay (automated activated partial thromboplastin time [APTT] from Trinity Biotech, Siemens BCS‐XP). For PD data, TGA was performed using platelet‐poor plasma samples prepared according to a standardized protocol . Blood samples were drawn in tubes containing 1.45 μmol/L corn trypsin inhibitor (Haematologic Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…For PD data, TGA was performed using platelet-poor plasma samples prepared according to a standardized protocol. 8 Blood samples were drawn in tubes containing 1.45 μmol/L corn trypsin inhibitor (Haematologic Technologies). Thrombin generation was measured using the calibrated automated thrombin generation test (CAT).…”
Section: Study Outcomesmentioning
confidence: 99%
See 1 more Smart Citation